Apoptose na Cidade Verde: suicídios em Teresina na primeira década do século 21 - Araújo Júnior, Benedito Carlos de (2014)
In the first decade of the 21st century, a wave of suicides fell over Teresina. 562 incidents were reported to the Ministry of Health. Youth were the main victims, with 30% of cases in the range 15-24 years. The city is the capital of Piauí, located in the Brazilian Northeast, a state that had the highest growth rate of suicides in the country, from 2001 to 2010. Influenced by indigenous tradition of the place, hanging is the method most used in Teresina. The rope and similar artifacts are used in 56% of deaths by voluntary asphyxiation and ease of access to the method hinders preventive actions, actions that were never adopted by the local authorities. Suicide is overlooked as an important cause of mortality despite killing more than AIDS, leishmaniasis and dengue epidemics which are considered priority in municipal health policy. The fight against dengue fever, which killed 11 people in the decade under study, promotes permanent educational campaigns aired in the media and has the brigades of health workers who work in direct contact with the inhabitants. For Suicide Prevention, which killed 51 times more than dengue, there are no policies. The taboo around suicide keeps society silenced, the media did not debate the matter by the belief that vulnerable individuals would be induced to commit the act of suicide and the State excuses itself from dealing with the complexity of emotional problems. The prevention program of the World Health Organization, established in 1999, has not been successful. The numbers continue to advance in the world. If they persist in the dark, suicide continues to claim victims, lulled by the global financial crisis, the globalization that erodes traditional cultures, the lifestyle of Western civilization, which made promises of well -being and unlimited progress, and failed. The people of Teresina deluded themselves with the singing of modernity, emptied itself of traditions, and it received in return disintegrated, disappointed, and disoriented individuals